(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This study critically examines St. Augustine’s Just War Theory and its implications in the context of the Israel-Gaza conflict, a complex and enduring geopolitical struggle. Augustine’s theory, one of the foundational texts in Christian ethics, outlines specific criteria for when war is morally justifiable, including just cause, right intention, legitimate authority, proportionality, and the pursuit of lasting peace. In this analysis, these principles are used as a framework to assess the actions of both Israel and Gaza, particularly focusing on military engagements, civilian casualties, and claims of self-defense. Through a qualitative methodology that combines historical, theological, and contemporary conflict analysis, the research evaluates how well the conflict aligns with Augustine’s ethical standards. The findings reveal that, while both parties often cite self-defense as a just cause, significant ethical challenges arise, particularly regarding the proportionality of force and the protection of non-combatants. Augustine’s emphasis on peace as the ultimate goal of any just war is contrasted with the ongoing cycle of violence, raising questions about whether either side is genuinely pursuing a peaceful resolution. Additionally, the issue of legitimate authority complicates the application of Augustine’s theory in a conflict involving state and non-state actors. The study concludes that while Augustine’s Just War Theory remains a valuable tool for ethical reflection, its application to modern asymmetric conflicts, such as the Israel-Gaza war, requires careful consideration of the unique challenges posed by contemporary warfare. This research underscores the need for reinterpreting ancient ethical frameworks in light of current geopolitical realities.